Some aspects of the project activity of philologists in the continuous education system - Olga Strelnyk (Kazimierz Wielki University, 2018)
The article is devoted to a detailed analysis of pedagogical design and development of basic principles of its implementation in the educational process, as well as the characteristics of the main subjects of pedagogical design. It is interesting and fresh to look at the definition of pedagogical design and pedagogical ideal within the cultural approach. The main conditions for ensuring a high level of training of philologists are the ability to project the system of continuous education, as well as to interact with all subjects of the pedagogical process.